AI Chatbots and EFL Learners’ Risk-Taking in Oral Communication: A Scoping Review - Wang, Xiaxia; Meng, Yu (Universitas Sulawesi Barat, 2026)
Research examining the role of AI-powered chatbots in promoting risk-taking in oral communication remains limited. This scoping review explored the interplay between AI-powered chatbots, risk-taking, and oral communication development among English as a Foreign Language (EFL) learners. Guided by the five-stage framework of Arksey and O’Malley and the PRISMA-ScR reporting guidelines, it systematically mapped and synthesized empirical studies retrieved from Web of Science, Scopus, and ProQuest. The analysis of 24 studies, including 18 on AI chatbots and 6 on risk-taking, generated three main findings. First, AI-powered chatbots effectively improved EFL learners’ oral communication skills by increasing practice opportunities, providing instant feedback, and creating a low-anxiety environment. Second, risk-taking was positively associated with oral proficiency, primarily by increasing the frequency of output and fostering a positive attitude toward errors. Third, a critical synthesis revealed that the core affordances of chatbots align with the key barriers to risk-taking, positioning them as a potential pedagogical practice to encourage risk-taking by reducing anxiety, boosting self-confidence, and prioritizing meaning-focused communication. Overall, the review highlights the importance of chatbot-mediated learning not only as a tool for linguistic practice but also as an affective scaffold that supports learners’ engagement in oral communication. Additionally, the findings underscore the need for chatbot designs that move beyond controlled practice and increase the simulation of real-life, risk-provoking communicative situations. By incorporating open-ended tasks and contextually authentic interactions, chatbots may better prepare learners to transfer risk-taking behaviors from low-stakes digital environments to real EFL classroom contexts.